1981
DOI: 10.1111/j.1651-2227.1981.tb05731.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 17-Ketosteroids in Cystic Fibrosis

Abstract: ABSTRACT. Pedersen, P. S., Flensborg, E. W. and Johnsen, S. G. (University Clinic of Paediatrics (TG), Rigshospitaiet and the Hormone Department, Statens Seruminstitut, Copenhagen, Denmark). Individual 17‐ketosteroids in Cystic Fibrosis. Acta Paediatr Scand, 70: 507,.–Data are presented for chromatographically separated urinary 17‐ketosteroids from 184 normal children and 106 children suffering from cystic fibrosis. In the latter group the 5β‐metabolites, 11‐hydroxy‐ethiocholanolone and 11‐keto‐ethiocholanolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…These findings may indicate the increased activity of 5α/5β ratio, which is supported by the increased activity of 5α-reductase, expressed by 11β-OH-Et/11β-OH-An ratio. Similar to the previous study, this difference between CF and controls was more pronounced in boys ( 65 ). However, the activity of SRD5A is the degradation of corticosterone metabolites (THB/5αTHB ratio) and conversion of testosterone to the most potent androgen dihydrotestosterone was lower.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings may indicate the increased activity of 5α/5β ratio, which is supported by the increased activity of 5α-reductase, expressed by 11β-OH-Et/11β-OH-An ratio. Similar to the previous study, this difference between CF and controls was more pronounced in boys ( 65 ). However, the activity of SRD5A is the degradation of corticosterone metabolites (THB/5αTHB ratio) and conversion of testosterone to the most potent androgen dihydrotestosterone was lower.…”
Section: Discussionsupporting
confidence: 90%
“…These two hormones are produced mainly by the gonads or during peripheral conversion, so the impact of reduced adrenal activity is less evident and/or other factors may play a role, as impairment of liver function and changes in enzyme activities. As in previous reports, we found a significant decrease in the secretion of 11-oxysteroids as 11b-OH-An and 11b-OH-Et in CF, but unlike those studies, we did not observe a decline in 11-oxo-Et (65). 11b-OH-Et and 11-oxo-Et, compounds with 5b-configuration, are almost exclusively metabolites of cortisol and cortisone, while the 5a-compound, 11b-OH-An, largely are derived from the reduction of 11-b-OH-androstenedione and to a lesser extent from An.…”
Section: Discussioncontrasting
confidence: 65%
“…We did not observe any effect of IFN-on the antibody-mediated response after 2 weeks [19,29]. This is not surprising, however, since in the 'natural course' of chronic P. aeruginosa lung infection in rats, IgM antibodies peak 1 week after challenge [18], whereas the IgG and IgA antibody responses reach highest levels from 4 to 13 weeks after challenge [18].…”
Section: Discussionmentioning
confidence: 67%
“…Recently, Moss et al [17] have shown preliminary evidence of selective expansion of Th2-like cells in CF patients measured by ELISA when CD4 clones from peripheral blood were mitogen-stimulated. One may speculate whether such differences in the T cell response could be due to differences in secreted steroid hormones among the patients [29]. Dehydroepiandrosterone (DHEA) has been shown to stimulate Th1 cells, leading to a reduced antibody response, whereas 1,25-dihydroxycholecalciferol stimulates Th2 cells and downregulates Th1 cells, leading to an increased antibody response [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moss et al (188) have shown preliminary evidence of selective expansion of TH2-like cells in C F patients when CD4+ clones were mitogen stimulated. One could speculate whether such differences in theT-cell response could be due to differences in secreted steroid hormones among the patients (199), since dehydroepiandrosterone (androgen) has been shown to stimulate THl cells leading to reduced antibody response, whereas 1,25-dihydroxycholecalciferol (vitamin D3) stimulates TH2 cells and down-regulates TH1 cells, leading to increased antibody response (240). This predominance of TH2-like immune response in CF patients is fbrther supported by two studies (153,236) which showed that C F patients had increased serum and sputum levels of the eosinophil cationic protein, indicating activation of eosinophils, in accordance with the activity of IL-3 and IL-5 (TH2 cytokines) which are increased in CF (271).…”
Section: Inteuferon-y Treatment Thi -Th2 Responsesmentioning
confidence: 99%